2007
DOI: 10.1007/s11661-006-9052-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transformation Annealing: a Novel Method for Grain Refinement of Cold-Rolled Low-Carbon Steels

Abstract: A novel heat treatment, rapid transformation annealing (RTA) is introduced, which uses the refining effect of the phase transformation during recrystallization annealing. The RTA is comprised of rapid heating including the full or partial phase transformation of cold-rolled, nonrecrystallized, or partly recrystallized a microstructure to c microstructure combined with subsequent rapid cooling to ambient temperature. In this way, a substantial grain refinement compared to conventional industrial annealing of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…However, this approach would be applicable to hot-rolled products rather than coldrolled and coated sheets that are of primary interest to the current work. Rapid heating and cooling experiments have also been used to develop very fine structures in steels using rapid transformation annealing (RTA) 15) and flash processing. 16) Andrade-Carozzo and Jacques 17) showed that rapid heating of an initial cold-rolled ferrite-pearlite structure into the intercritical annealing region results in grain refinement in the final dual phase structures of a Nb-bearing low carbon steel.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach would be applicable to hot-rolled products rather than coldrolled and coated sheets that are of primary interest to the current work. Rapid heating and cooling experiments have also been used to develop very fine structures in steels using rapid transformation annealing (RTA) 15) and flash processing. 16) Andrade-Carozzo and Jacques 17) showed that rapid heating of an initial cold-rolled ferrite-pearlite structure into the intercritical annealing region results in grain refinement in the final dual phase structures of a Nb-bearing low carbon steel.…”
Section: Introductionmentioning
confidence: 99%
“…As the interaction occurs, the kinetics of recrystallization and transformation are increased. 3,6,13,16,21 The austenite phase nucleates first at the deformed ferrite grain boundaries. 22 On the other hand, austenite provides a preferred recrystal- lization nucleation site for the non-recrystallized ferrite.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] This condition provides the ability to control the microstructure by means of the simultaneous occurrence of recrystallization and phase transformation. URA shifts the start temperature of recrystallization to higher values near and above Ac 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of rapid heating during continuous annealing, ferrite recrystallization is strongly suppressed during the heating stage, while the austenite formation and its distribution are strongly influenced by overlapping of the processes of recrystallization and austenitization and thus it could refine the grain structure, to improve both strength and ductility at MATEC Web of Conferences the same time [8]. The purpose of this study was to explore the influence of higher heating rate on the microstructure and tensile behavior of DP590 steel.…”
Section: Introductionmentioning
confidence: 99%